Engine testing : theory and practice - Plint, M. A. (Michael Alexander) (Butterworth-Heinemann, 1995)
Engine Testing: Theory and Practice brings together the information on both the theory and practice of engine testing that engineers in this field must have available. Organized into 19 chapters, this book begins with a description of the engine test cell, including the salient features of its main types. Subsequent chapters deal with the other main components of an engine testing installation: the control room and the ventilation systems. Other chapters discuss the essential features of a test installation fuel supply system, as well as the characteristics, advantages, and disadvantages of th.